Long-term omega-3 supplementation modulates behavior, hippocampal fatty acid concentration, neuronal progenitor proliferation and central TNF-α expression in 7 month old unchallenged mice - Grundy, Trent; Toben, Catherine; Jaehne, Emily J.; Corrigan, Frances; Baune, Bernhard T. (Frontiers in Cellular Neuroscience, 2014)
Dietary polyunsaturated fatty acid (PUFA) manipulation is being investigated as a potential therapeutic supplement to reduce the risk of developing age-related cognitive decline (ARCD). Animal studies suggest that high omega (Ω)-3 and low Ω-6 dietary content reduces cognitive decline by decreasing central nervous system (CNS) inflammation and modifying neuroimmune activity. However, no previous studies have investigated the long term effects of Ω-3 and Ω-6 dietary levels in healthy aging mice leaving the important question about the preventive effects of Ω-3 and Ω-6 on behavior and underlying molecular pathways unaddressed. We aimed to investigate the efficacy of long-term Ω-3 and Ω-6 PUFA dietary supplementation in mature adult C57BL/6 mice. We measured the effect of low, medium and high Ω-3:Ω-6 dietary ratio, given from the age of 3 to 7 months, on anxiety and cognition-like behavior, hippocampal tissue expression of TNF-α, markers of neuronal progenitor proliferation and gliogenesis and serum cytokine concentration. Our results show that a higher Ω-3:Ω-6 PUFA diet ratio increased hippocampal PUFA, increased anxiety, improved hippocampal dependent spatial memory and reduced hippocampal TNF-α levels compared to a low Ω-3:Ω-6 diet. Furthermore, serum TNF-α concentration was reduced in the higher Ω-3:Ω-6 PUFA ratio supplementation group while expression of the neuronal progenitor proliferation markers KI67 and doublecortin (DCX) was increased in the dentate gyrus as opposed to the low Ω-3:Ω-6 group. Conversely, Ω-3:Ω-6 dietary PUFA ratio had no significant effect on astrocyte or microglia number or cell death in the dentate gyrus. These results suggest that supplementation of PUFAs may delay ageing effects on cognitive function in unchallenged mature adult C57BL/6 mice. This effect is possibly induced by increasing neuronal progenitor proliferation and reducing TNF-α.